Pengaruh Elemen Ekuitas Merek Terhadap Keputusan Pembelian Produk Kopi Sadari Kopi Di Kota Surakarta - Salman Alfarisi; Nuning Setyowati; Setyowati Setyowati (JURNAL AGRIBISNIS TERPADU, 2019)
This research aims to analyze the influence of brand awareness, brand association, perceived quality, and brand loyalty on Purchase Decision of Sadari Kopi Coffee Products in Surakarta. The basic method of this research is descriptive analysis and survey. Determination of the research area using a purposive method, while determination of the sample using a non – probability sampling method with purposive sampling type. The sample consists of 100 respondents. The data collection tool uses a questionnaire distributed directly to respondents. Instrument testing (validity and reliability test) and data analysis (multiple linear resression analysis, classic assumption test, hypothesis test) using SPSS 25.0. The result proved that brand awareness, brand association, perceived quality, and brand loyalty simultaneously have a positive influence on purchase decision of Sadari Kopi coffee products in Surakarta. Brand association and brand loyalty partially has a positive effect on purchase decision of Sadari Kopi coffee products in Surakarta, but brand awareness and perceived quality partially has no significant effect on purchase decision of Sadari Kopi coffee products in Surakarta. Consumer loyalty can be increased by creating a member card and loyalty program. Sadari Kopi is expected to maintain and enhance brand associations by increasing the perception of positive value to consumers through coffee to go concept. This can be enhanced by introducing and educating the concept of coffee to go through the Sadari Kopi social media account.